Morphological evaluation of soft palate in various stages of oral submucous fibrosis and normal individuals: A digital cephalometric study - Supriya Rathore; Neelkant Patil; Mohit Sareen; Manoj Meena; Pallavi Baghla; Nitesh Tyagi (Wolters Kluwer Medknow Publications, 2019)
Aim of Study: The aim of the study was to evaluate the morphology of soft palate in different stages of oral submucous fibrosis (OSMF) patients using digital lateral cephalogram. Materials and Methods: Total 100 participants were enrolled for the study. They were divided into two groups, Group 1 consisted of first 50 patients diagnosed with OSMF and Group 2 consisted of first 50 non-OSMF patients. Results: Morphology of soft palate was divided into eight types and was compared. Leaf shape (Type 1) was found to be most common and bifid shape least common. It was observed that as the grade of OSMF increases, the size of soft palate also shortens and becomes bulkier as compared to initial stages or non-OSMF group, and results were highly significant with a P value of > 0.05. Conclusion: The soft palate has variable radiographic appearances on lateral cephalometry. The classification system and statistical findings here may help the research of velopharyngeal closure in cleft palate individuals and etiological study of obstructive sleep apnea syndrome and other conditions.